Modified Granular Activated Carbon: A Carrier for the Recovery of Nickel Ions from Aqueous Wastes - D. Satapathy; G.S. Natarajan; Raja Sen (Adsorption Science & Technology)
Granular Activated Carbon (GAC) is widely used for the removal and recovery of toxic pollutants including metals because of its low cost and high affinity towards the scavenging of metal ions. Activated carbon derived from bituminous coal is preferred for wastewater treatment due to its considerable hardness, a characteristic needed to keep down handling losses during re-activation. Commercial grade carbon, viz. Filtrasorb (F-400), was used in the present work. The scavenging of precious metals such as nickel onto GAC was studied and a possible attempt made to recover the adsorbed Ni 2+ ions through the use of some suitable leaching processes. As part of the study, the role of complexing agents on the surface of the carbon was also investigated. The use of organic complexing agents such as oxine and 2-methyloxine in the recovery process was found to be promising. In addition, the surface of the carbon was modified with suitable oxidising agents that proved to be more effective than chelating agents. Several attempts were made to optimise the recovery of metal ions by carrying out experiments with oxidising agents in order to obtain maximum recovery from the minimum quantity of carbon. Experiments with nitric acid indicated that not only was the carbon surface modified but such modification also helped in carbon regeneration.